A survey of fitness landscape analysis for optimization - Zou, Feng; Chen, Debao; Liu, Hui; Cao, Siyu; Ji, Xuying; Zhang, Yan (Neurocomputing (Amsterdam), 2022)
•FLA has attracted attention of researchers for its research significance and application.•This paper attempts to give an overview of fitness landscape analysis for optimization.•Future research works are discussed and given in four aspects. Over past few decades, as a powerful analytical tool to characterize the fitness landscape of a problem, fitness landscape analysis (FLA) has been widely concerned and utilized for all kinds of optimization areas. Since its introduction by Sewell Wright in 1932, FLA has attracted more and more attention of researchers for its research significance and application value such as an intuitive understanding features of complex optimization problems, explaining evolutionary algorithm behavior, assessing performances of algorithms, and guiding selections and/or configures of algorithms. This paper attempts to give an overview of fitness landscape analysis and its typical application for optimization so far. We hope that this survey can help to understand features of complex optimization problems in depth and thus to improve the certain algorithm performance of for a given optimization problem.